Advanced diffusion MRI and image texture analysis detect widespread brain structural differences between relapsing-remitting and secondary progressive multiple sclerosis - Oladosu, Olayinka; Liu, Wei-Qiao; Brown, Lenora; Pike, Bruce G.; Metz, Luanne M.; Zhang, Yunyan (Frontiers in Human Neuroscience, 2022)
Introduction: Disease development in multiple sclerosis (MS) causes dramatic structural changes but the exact changing patterns are unclear. Our objective is to investigate the differences in brain structure locally and spatially between relapsing-remitting MS (RRMS) and its advanced form, secondary progressive MS (SPMS), through advanced analysis of diffusion magnetic resonance imaging (MRI) and image texture. Methods: 20 RRMS and 9 SPMS patients from 2 datasets underwent 3T anatomical and diffusion tensor imaging (DTI). The DTI was harmonized, augmented, and then modeled, which generated 6 voxel- and sub-voxel-scale measures. Texture analysis focused on T2 and FLAIR MRI, which produced 2 phase-based measures: phase congruency and weighted mean phase. Data analysis was 3 folds: histogram analysis of whole-brain normal appearing white matter (NAWM); region of interest (ROI) analysis of NAWM and lesions within 3 critical white matter tracts: corpus callosum, corticospinal tract, and optic radiation; and along-tract statistics. Further, by calculating the z-score of core-rim pathology within lesions based on diffusion measures, we developed a novel method to define chronic active lesions and compared them between cohorts. Results: Histogram features from all diffusion and all but one texture measure differentiated RRMS and SPMS. Within-tract ROI analysis detected cohort differences in both NAWM and lesions of the corpus callosum body in 3 measures of neurite orientation and anisotropy. Along-tract statistics detected cohort differences from multiple measures, particularly lesion extent, which increased significantly in SPMS in posterior corpus callosum and optic radiations. The number of chronic active lesions were also significantly higher (by 5% – 20% over z-scores 0.5 and 1.0) in SPMS than RRMS based on diffusion anisotropy, neurite content, and diameter. Conclusion: Advanced diffusion MRI and texture analysis may be promising approaches for thorough understanding of brain structural changes from RRMS to SPMS thereby providing new insight into disease development mechanisms in MS.